Value Chain Analysis of Honey Sub-sector in Nepal - Bhandari, Padam Lal; Kattel, Rishi Ram (International Journal of Applied Sciences and Biotechnology, 2020)
Beekeeping is a low investment and low input business enterprise with immediate return. However, very few researches has been done on value chain analysis of honey sub-sector in Nepal. Such a backdrop, this research gauges the value chain of honey in Nepal focusing value chain function, actors/products flow and enabling business in 2018. Both primary and secondary information were collected using different research instruments in 2018. This study revealed that Apis cerana was the major honey-bee reared in Pyuthan district and about 50% youth were engaged in beekeeping business. Each household have an average of 32 hives ranging from 15 to 80 hives. Average 32 kg honey was consumed at HHs level and 239 kg was sold. The average wholesale rate of honey at farm gate was about NPR 400-450 (USD 3.6-4.1) per kg with the retail price rate was NPR 500 (USD 4.5). An average income earned from honey sale was NPR 60000 (USD 545) per annum ranging from NPR 20000 to 120000. Majority of the beekeepers received training whereas none of them have done insurance. About 55% of the beekeepers have taken loan from saving groups and cooperatives or MFIs. There has not any provision of grading, processing and labelling of the product at producer’s point in the study area. The main threats of beekeeping came from loss of habitat, disease, pest and enemies. This research suggests to develop upgrading practices with facilitation of basic value chain practices for promotion of high-quality Nepali honey at global markets. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 83-95